Verbascum golawanense (Scrophulariaceae), a new species from Van, Turkey - Firat, Mehmet (Phytotaxa, 2017)
Verbascum golawanense is described and illustrated as a new species from Van, Turkey. The diagnostic morphological characters of this taxon and the morphologically similar species V. lasianthum are discussed. A distribution map of the new species and V. lasianthum is also provided.